Research trends and progress in the field of metal materials and bone repair: Comprehensive bibliometric and visual analysis (2012–2021) - Xu, Zhuoran (Frontiers in Materials, 2022)
Abstract Purpose: The treatment of bone repair has always been a focus of research. In recent years, new metals have been increasingly used for bone repair, and many related studies have been published. However, until now, there has been no bibliometric analysis of these publications. This study uses bibliometrics to evaluate the current research status in this field to predict future research hotspots and development trends and promote the development and progress of this field. Methods: Global publications on metal materials and bone repair from January 2012 to December 2021 were extracted from the Web of Science database. Microsoft Excel 2016, GraphPad Prism 8, VOSviewer, and CiteSpace were employed to perform the bibliometric study and data visualization. Results: China contributed the most publications and had the most citations and H-index, especially in the last five years. The journal Materials Science & Engineering C-Materials for Biological Applications published the most papers. The Chinese Academy of Sciences had the most publications among all institutions. The top 10 articles by citations mainly focused on porous polymer scaffolds and the metals zinc and magnesium. Conclusions: We predict that the total number of global publications will grow in the future according to the relative research interest. Importantly, the current research focus has shifted from metal materials to osteogenic mechanisms. Porous scaffolds, degradation rate, tissue engineering, angiogenesis, and stem cells could be research hotspots in the future.